Evaluating lexical cohesion in Nigerian newspaper genres: focus on the editorials - Malah, Zubairu; Tan, Helen; Md Rashid, Sabariah (Australian International Academic Centre, 2017)
Applied linguists paying scholarly attention to newspaper genres have often argued that findings emerging from such studies would be of pedagogical significance because most of the newspaper genres share certain conventional features with school genres. Similarly, this study explored lexical cohesion in newspaper editorials, and it is understood that the findings could help learners in handling persuasive writings. The study sought to identify the dominant sources of lexical cohesion in the editorials, and also to examine how lexical cohesion is utilized to achieve coherence in the editorials. Drawing on Systemic Functional Linguistics (SFL), the study applied Eggins’ (2004) model of lexical cohesion and analyzed 30 editorial texts of 20, 354 words drawn from three major Nigerian newspapers: The Guardian, The Nation, and Vanguard. The analysis revealed 2, 685 ties across 849 sentences. The data demonstrated that the major types of lexical cohesion in the editorials include: repetition (49.5%), expectancy relations (15. 8%), class/sub-class (11%), and synonymy (10.8%). It was further revealed that lexical cohesion devices, which formed into chains (586) and isolated ties (837), were utilized in building coherence in the editorial texts. It was finally shown how findings of the study could be beneficial in ESP, EAP, and EGP learning, especially in persuasive writings.